2000
DOI: 10.1007/bf02344867
|View full text |Cite
|
Sign up to set email alerts
|

A method for turbulent noise estimation in voiced signals

Abstract: In this article a new acoustic parameter is introduced and it is shown that it may serve as an indicator of laryngeal function. It is termed the turbulent noise index (TNI) and is defined as 100(1 - Rmax), where Rmax is the mean value of the maximum correlation coefficient between each pair of consecutive glottal cycles in the voiced signal. A method for its calculation is described. Experiments with synthetic and natural voice signals show that TNI is almost independent of frequency modulation noise and ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In these studies, the two-dimensional model is considered as the reference in the predictions comparison. However, since glottal flow is three-dimensional and can develop a turbulent character [17], it is questionable whether twodimensional laminar flow models could provide an appropriate validation for simpler models.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the two-dimensional model is considered as the reference in the predictions comparison. However, since glottal flow is three-dimensional and can develop a turbulent character [17], it is questionable whether twodimensional laminar flow models could provide an appropriate validation for simpler models.…”
Section: Introductionmentioning
confidence: 99%
“…Normalized noise energy (NNE, dB) is a parameter influenced by frequency and amplitude variations and highly sensitive to changes in jitter and shimmer. It was suggested that NNE is extremely helpful in assessing breathy voice [32]. Patients treated with open cordectomy had confirmed incomplete glottic occlusion in more cases than the ones treated with endoscopic laser cordectomy.…”
Section: Discussionmentioning
confidence: 99%
“…After having selected only the speech frames, it is necessary to classify them into turbulent or nonturbulent. To provide this classification we used an algorithm based on a different implementation of the turbulent noise index (TNI) reported in (Mitev, 2000). In the scope of this work, the aim of the TNI parameter was to segment the frames according to the degree of turbulence, not exactly into voiced and unvoiced.…”
Section: Turbulence Segmentationmentioning
confidence: 99%
“…Among the acoustic measures, the most widely used are jitter (changes in pitch period with time) and shimmer (changes in amplitude with time) (Deliyski, 1993), harmonic-to-noise ratio (HNR) (Krom, 1993), cepstral peak prominence (CPP) (Hillenbrand, 1996), glottal to noise excitation ratio (GNE) (Michaelis, 1997), normalized noise energy (NNE) (Kasuya, 1986), soft phonation index (SPI) (Deliyski, 1993), and voice turbulence index (VTI) (Mitev, 2000). Over the years, several systems combining various acoustic measures and different classifiers have been designed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation